The Validity of Dispute Resolution Clauses in Electronic Contracts under Indonesian Civil Law - Amirah Dwi Subarkah (Faculty of Law-Universitas Bandar Lampung, 2026)
The rapid growth of electronic commerce has made standard-form electronic contracts, together with the dispute resolution clauses embedded in them, a common yet legally contested feature of everyday transactions. This article examines the validity of dispute resolution clauses in electronic contracts, such as choice of forum, choice of law, arbitration, and online dispute resolution, from the perspective of Indonesian civil law. Previous studies have examined the validity of electronic contracts in general and the position of choice-of-law clauses in cross-border digital transactions, but comparatively little attention has been paid to the validity requirements and enforceability of dispute resolution clauses that are unilaterally drafted into standard-form electronic contracts. Using a normative juridical method with statutory, conceptual, and comparative approaches, this article finds that a dispute resolution clause in an electronic contract is valid so long as it fulfills the elements of a valid agreement under Article 1320 of the Indonesian Civil Code and does not violate the principle of good faith under Article 1338 or mandatory consumer protection norms. Clauses that unreasonably restrict consumer access to justice, that are concealed from a party's reasonable notice, or that rely on an internal online dispute resolution mechanism lacking independence may be declared void or non-binding. The article recommends clearer regulatory standards on the form, disclosure, and procedural fairness of such clauses in electronic standard contracts. Keywords: Electronic Contract; Dispute Resolution Clause; Validity; Standard Clause.